(untitled) (Eurasian Journal of Engineering and Technology, 2022)
The article provides a variety of obtaining synthetic fuel from biological municipal waste. As well as increasing the role of various alcohols in internal combustion engines, dehydration methods for obtaining dimethyl ethers from methanol.